When Diversity Backfires: The Asymmetric Role of Multicultural Diversity on Brand Perception - Uduehi, Esther; Saint Clair, Julian K; Hamilton, Mitchell; Reed, Americus (Journal of Consumer Research, 2025)
Abstract Brands are expanding their market to new consumers by displaying cultural diversity in marketing campaigns—but the risks are unclear. This article explores the role of the brand’s characteristics in multicultural diversity. Our findings suggest that when brands launch a new multicultural diversity campaign, it may be well-received if the brand’s original focus was on the needs of nonmarginalized consumers. However, for brands with a focus on the needs of marginalized consumers (i.e., marginalized-focused brands), such a campaign may be perceived as selling out, thereby negatively impacting consumers’ reactions. Six studies with Black and White U.S. consumers explore this novel “sellout effect” across various product categories and for consequential behaviors. Inclusion is identified as a key mechanism, mitigation strategies are explored, and implications for theory and practice are discussed. Findings highlight the importance of diversity marketing, understanding marginalization for consumers and brands, and the need for research that considers race and ethnicity.